Pengaruh Capital Expenditure, Sales Growth, Revaluation Fixed Asset dan Leverage terhadap Kinerja Perusahaan Transportasi - Ulfia Nabila Istiqomah; Hadi Ismanto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to test and analyze the effect of capital expenditure, sales growth, revaluation of fixed assets and leverage on company performance. The population in this study includes 46 transportation service sectorcompanies listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique used purposive sampling so that a research sample of 42 manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period was obtained. The analysis technique uses a fixed effect model. The results in this studyindicate that the sales growth variable has a significant positive effect on company performance,while revaluation of fixed assets and leverage has a significant negative effect on company performance, and capital expenditure have no effect on company performance.